2015
DOI: 10.1158/0008-5472.can-15-1320
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Myeloma Impairs Bone Marrow Localization of Effector Natural Killer Cells by Altering the Chemokine Microenvironment

Abstract: Natural killer (NK) cells are key innate immune effectors against multiple myeloma, their activity declining in multiple myeloma patients with disease progression. To identify the mechanisms underlying NK cell functional impairment, we characterized the distribution of functionally distinct NK cell subsets in the bone marrow of multiple myeloma-bearing mice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(96 citation statements)
references
References 48 publications
5
91
0
Order By: Relevance
“…44 Herein, we further confirmed in vivo the involvement of NK cells during tumor surveillance in melphalan-treated tumor-bearing mice by depleting NK1.1 C cells. Mice were intraperitoneally injected with anti-NK1.1 monoclonal antibody and tumor growth was shown to be higher in both PBS-and melphalan-treated NK1.1 C cell-depleted tumor-bearing mice as compared to nondepleted mice (Fig.…”
Section: Melphalan-treated MM Cells More Efficiently Trigger Nk Cell supporting
confidence: 62%
See 1 more Smart Citation
“…44 Herein, we further confirmed in vivo the involvement of NK cells during tumor surveillance in melphalan-treated tumor-bearing mice by depleting NK1.1 C cells. Mice were intraperitoneally injected with anti-NK1.1 monoclonal antibody and tumor growth was shown to be higher in both PBS-and melphalan-treated NK1.1 C cell-depleted tumor-bearing mice as compared to nondepleted mice (Fig.…”
Section: Melphalan-treated MM Cells More Efficiently Trigger Nk Cell supporting
confidence: 62%
“…We chose 3 weeks after tumor injection as experimental end point to avoid the impairment of NK cell effector functions due to MM-derived alteration of NK cell trafficking as previously reported by our group. 44 Fifty micrograms of melphalan in phosphate-buffered saline (PBS), or PBS alone as sham, were intraperitoneally administered to tumor-bearing mice as illustrated in Fig. 1.…”
Section: Nkg2d and Dnam-1 Ligand Expression Is Enhanced On MM Cells Bmentioning
confidence: 99%
“…As such the role of the chemokine system in controlling the distribution of T cells within the lymphoid compartment in patients with myeloma is likely to be highly complex. Ponzetta et al have recently shown that administration of myeloma cells to immunodeficient mice leads to an increase in CXCL9 and CXCL10 within the murine bone marrow, supporting a direct role for tumour cells in the generation of inflammatory mediators [47]. In addition they also observed increased levels of CXCL10 within the bone marrow of patients with multiple myeloma and this was correlated with a decrease in the number of CXCR3+ NK cells within blood.…”
Section: Oncotarget 30389 Wwwimpactjournalscom/oncotargetmentioning
confidence: 90%
“…As such, CXCL9 [42], CXCL12 [28] and CCL3 [43] have been shown to be produced by myeloma plasma cells whereas stromal cells have been shown to produce a range of chemokines, including CCL2, CCL7, CCL8 and CCL13 from osteoclasts [44], CXCL8, CXCL11, CXCL12 and CCL2 from endothelial cells and bone marrow fibroblasts producing CXCL12 [28]. The CXCR 4/CXCR7/ (SDF) axis has been shown to be important in the recruitment of monocytic lineage cells and increased levels of CXCL12 are believed to promote the differentiation of M2 macrophages [28,30,27,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation